2019
DOI: 10.1007/978-981-13-3131-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Southeast Asia and International Trade: Continuity and Change in Historical Perspective

Abstract: This chapter provides a general overview of the relations between international trade and the economy of Southeast Asia from a long-term perspective. After the short description about the relationships between natural endowments and international trade of Southeast Asia before the European arrival, this chapter is devoted to an analysis of international trade of Southeast Asia since the sixteenth century by focusing on the economic influences of international trade on the Southeast Asian economy and society. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…They prefer human-machine collaboration in Southeast Asia's navigation. Needless to say, the weather of south-east Asia is not preferable, unpredicted heavy weather happens there several times annually (Shimada 2019). It is assumed that, navigation in harsh weather and complex geographic area are the reasons for non-reliability on fully autonomous (Ziajka-Poznańska and Montewka 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They prefer human-machine collaboration in Southeast Asia's navigation. Needless to say, the weather of south-east Asia is not preferable, unpredicted heavy weather happens there several times annually (Shimada 2019). It is assumed that, navigation in harsh weather and complex geographic area are the reasons for non-reliability on fully autonomous (Ziajka-Poznańska and Montewka 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The south-east Asian region is considered as the center of gravity for Indro-pacific connectivity as the geographical properties construct the connectivity network for the Indian and Pacific oceans routes (Wróbel et al 2020).This region historically engaged in two types of maritime trade exchange: intra-Asian and intra-regional (Shimada 2019).…”
Section: Autonomous Vessel For South-east Asia's Routementioning
confidence: 99%
“…Similarly, some studies have concluded that intra-Asian trade during the high colonial period was smaller than long-distance trade and was mainly driven by Western powers. Moreover, trade between neighboring countries only became a driver of East and Southeast Asian development in the 1970s (Shimada 2019). Finally, Sugihara (2019) demonstrated that intra-Asian trade rose from 27% to 70% of total trade from 1950 to 2014, whereas it only equated to 53% of trade in 1938.…”
Section: The Intensity Of Intra-asian Trade and Its Determinants: Con...mentioning
confidence: 99%
“…Overseas demands for products distributed from the interior, also the sizable income from profit given from transit trade promoted people to travel and stay in the lower places. Thus, emporium such Gresik (Java), Palembang in Sumatera, and Ayutthaya in Thailand were constructed to provide maritime trade (Shimada, 2019).…”
Section: Japanese Merchants In Southeast Asia In the 17 Th Centurymentioning
confidence: 99%
“…Thus, Southeast Asia trade grew along with Asian countries trade through intra-regional trade. Therefore, in the 15 th century, international maritime trade truly improved in global level and Southeast Asia economy also experienced changes (Shimada, 2019). The growth of Southeast Asian maritime trade between the 15 th and 17 th century promoted the appearance of stronger, centralized states drawing most of their revenues from trade (Reid, 2012).…”
Section: History Of Japan (From Tokugawa Times To the Presentmentioning
confidence: 99%